2015
DOI: 10.2807/1560-7917.es2015.20.4.21019
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Human Leptospirosis in Denmark, 1980 to 2012

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 18 publications
3
27
1
Order By: Relevance
“…This limited acquisition process in our patient cohort can be explained by the lifestyles of children in an industrialized country where involvement in other high-risk activities is substantially less common than in adults or children in resource-limited countries. In addition, unlike the previously reported seasonal pattern from developing countries (i.e., year-round occurrence with a peak in the postsummer season) [ 16 , 17 , 23 ], leptospirosis in our patients exclusively occurred from August to November, which is summer and fall, respectively, in Okinawa. We speculate that this limited seasonal pattern can be attributed to freshwater recreational activities among children on summer vacation and higher precipitation during this season in Okinawa.…”
Section: Discussioncontrasting
confidence: 87%
“…This limited acquisition process in our patient cohort can be explained by the lifestyles of children in an industrialized country where involvement in other high-risk activities is substantially less common than in adults or children in resource-limited countries. In addition, unlike the previously reported seasonal pattern from developing countries (i.e., year-round occurrence with a peak in the postsummer season) [ 16 , 17 , 23 ], leptospirosis in our patients exclusively occurred from August to November, which is summer and fall, respectively, in Okinawa. We speculate that this limited seasonal pattern can be attributed to freshwater recreational activities among children on summer vacation and higher precipitation during this season in Okinawa.…”
Section: Discussioncontrasting
confidence: 87%
“…Cases mainly acquired leptospirosis during recreational activities such as swimming and fishing, in contrast with other western European countries, where autochthonous leptospirosis infections are predominantly associated with occupational activities [13][14][15]. A possible explanation for the increase of autochthonous cases is the preceding mild winter of 2013 to 2014 followed by the warmest year in three centuries in Europe [16,17], possibly enabling rodents and also excreted Leptospira to better survive [2,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Switzerland lacks an adequate surveillance system for this disease because human cases are not subjected to mandatory report for more than 15 years. Data from Europe indicated that the highest rates of leptospirosis occur in summer and fall [ 13 , 14 ]. Likewise, all described patients in this study suffered from leptospirosis either in summer (Case 2 in September 2014, Case 3 in August 2014) or in fall (Case 1 in October 2014).…”
Section: Discussionmentioning
confidence: 99%